Develop a mobile app for F&B food ordering using i-Beacon protocol - Gopalakrishnan, Sailesh (Nanyang Technological University, 2023)
The report focuses on developing a mobile app for Food & Beverage (F&B) food ordering using i-Beacon protocol. It explores the potential of iBeacon technology in enhancing the dining experience by allowing customers to order directly to their tables in busy urban F&B establishments. The project involves designing an application interfacing with iBeacon-emitting beacons, utilizing Flutter for the front-end UI and Firebase for the database. The report details the implementation process, features such as user account management, ordering flow, and integration of beacons for location detection. The conclusion reflects on the learning outcomes and future improvements for the app.